Analysis of the Main Character in the Novel Eccedentesiast By Itakrn: A Literary Psychology Study - Munthe, Indriyani Rehulina Br; Sibagariang, Lastarida; Harahap, Nurhayati (Peneliti.net, 2023)
This research was motivated by an interest and desire to know more about the personality of the main character Canva in the novel EccedentesiasT by Itakrn. The aim of this research is to determine the personality of the main character Canva in the novel EccedentesiasT by Itakrn. The results of the research found several personalities experienced by the main character of Canva. The main character's personality type is 1) Accompaniment Process a) kind, b) humble, c) calm, d) disappointed, e) good memory, f) not calm, g) not easily discouraged, h) careless, 2) Emotional a) angry 3) Activities a) easy to open your heart, b) forgiving, c) affectionate, d) likes to share, e) likes to help.